Implementation of STEM integrated problem based learning model to improve student creativity - Zakiah, Rohmiati; Novia, Hera; Suwarma, Irma Rahma; Dahsah, Chanyah; Febriani, Febriani (WaPFi (Wahana Pendidikan Fisika), 2025)
The purpose of this study is to describe how the application of learning with a STEM integrated problem based learning model can improve students' creativity . This study uses a quantitative method with  a pre-experimental design in the form of a one group pre-test post-test design which was implemented in one of the high schools in Sumedang Regency. The sample in this study was 43 students in 10th grade at the school. The sampling technique used was purposive sampling. The data collection instrument used to measure students' creativity was Cognitive, Processes Associated with Creativity test ( CPAC  ) consisting of 8 statements related to the act and flow aspects were given during the pre-test and post-test , and the student creativity observation sheet to observe the emergence of student creativity during the learning process which includes aspects of flexibility, fluency, originality, elaboration, and clarification. In this study, learning was carried out using a problem-based learning model by integrating STEM elements in the momentum and impulse material  . Data analysis techniques to see the increase in student creativity using descriptive statistics, N-Gain calculations then The assessment result data was analyzed descriptively and then categorized. The results showed that the increase in student creativity based on the results of the n-gain analysis of the pre-test and post-test scores was 0.433 in the moderate criteria for the act and flow aspects, then for the flexibility, fluency, originality, elaboration, and clarification aspects it had good criteria with a percentage of 77.56%. So based on the analysis of the findings in the study, the application of the STEM integrated problem based learning model can increase student creativity